2022
DOI: 10.1590/1679-78257314
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Numerical Evaluation of Dry Precast Beam Column Connection with Embedded Bolts

Abstract: Precast dry connected frame systems are faster to construct with less erection efforts. These frame systems are considered non-emulate frame systems. The lateral load behaviour of these connections needs to be evaluated to ensure the desired performance. The performance of these dry connections with embedded bolts proposed was studied by finite elemental analysis. The nonlinear FEM analysis results obtained by considering appropriate elements, and material definition parameters, including failure and interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…In the field of precast concrete beam-column joints based on the bolt connection, more and more studies have found that dry connection beam-column joints have good seismic performance when the design is reasonable. 5 There are multiple methods were used in the study of precast concrete beam-column joints based on the bolt connection, including experiment, 12,13 finite-element simulation, 14 and theoretical derivation. 2,15 The experiment on prefabricated concrete beam-column joint based on the bolt connection was studied by Ding et al, 16 which showed that the precast concrete beam-column joint based on the bolt connection exhibited excellent performance in resisting seismic loading and good assembly efficiency.…”
mentioning
confidence: 99%
“…In the field of precast concrete beam-column joints based on the bolt connection, more and more studies have found that dry connection beam-column joints have good seismic performance when the design is reasonable. 5 There are multiple methods were used in the study of precast concrete beam-column joints based on the bolt connection, including experiment, 12,13 finite-element simulation, 14 and theoretical derivation. 2,15 The experiment on prefabricated concrete beam-column joint based on the bolt connection was studied by Ding et al, 16 which showed that the precast concrete beam-column joint based on the bolt connection exhibited excellent performance in resisting seismic loading and good assembly efficiency.…”
mentioning
confidence: 99%